(untitled) - Lewicki, Roy J. (Boston, MA., 2006)
Negotiation is a critical skill needed for effective management. NEGOTIATION 5/e explores the major concepts and theories of the psychology of bargaining and negotiation, and the dynamics of interpersonal and intergroup conflict and its resolution. It is relevant to a broad spectrum of management students, not only human resource management or industrial relations candidates.
Keywords: Negotiaton in business